Collection evaluation and the conspectus: Chimeras in Library cooperation?. Issue 4 (1st October 2016) - Schmidt, Janine
Abstract: Although collection measurement has been much practised by librarians, it is seldom linked to precise, qualitative and client-centred objectives. The RLG conspectus offers a methodology whose validity for Australia needs to be examined carefully. Program performance evaluation has already proved illuminating at the State Library of New South Wales. Collection evaluation is useful for cooperation if properly documented.